Peran Investasi Emas dan Aksesibilitas Pembiayaan dalam Meningkatkan Kesejahteraan Ekonomi Masyarakat Indonesia - Mardhiyah, Umi Rossy (Program Studi Ekonomi Syariah STAI Senori Tuban, 2025)
The consumer behavior of Indonesian people in spending money to meet their daily needs has become a common phenomenon, especially in the current digital era. Although online shopping through e-commerce provides convenience, many individuals become trapped in a cycle of waste by purchasing items they don't need. This research aims to explore the role of gold investment as a more productive alternative in improving the economic welfare of society. In the Sharia context, gold investment is not only considered a safe instrument but also a way to protect the value of wealth from inflation. Qualitative research methods were used to analyze gold investment practices in Indonesia, with a focus on accessibility and the potential profits offered. The research results show that gold investment can be a solution to overcome consumer behavior and improve people's financial welfare. By investing in gold, people can not only store wealth but also have assets that are easy to liquidate when needed. This research recommends that people be wiser in managing their finances by diverting consumer spending into more useful investments, such as gold, to achieve long-term prosperity.